A modified auxiliary agent composition for seawater degradation of plastics and application thereof

CN121592144BActive Publication Date: 2026-10-27BEIJING ZHONGKE KELAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202512051606.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-31
Publication Date
2026-10-27
Estimated Expiration
2045-12-31

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足之处,本发明的一个目的在于提供一种海水降解塑料用改性助剂组合物,其具有时序触发和动态平衡机制的改性助剂组合物,旨在实现塑料制品在服役期内性能稳定,而在废弃进入海水环境后能够被快速、可控地完全降解,从而解决现有海洋降解技术中存在的降解效率低、无法平衡服役期性能与降解速率、以及与现有加工工艺兼容性差等核心问题

Benefits of technology

降解高效且时序可控:独创的“内部加速、表面缓释”机制,实现了“先稳定服役,后快速降解”的智能响应。通过三重协同作用,可将材料在海水中的降解周期从数年缩短至数周,且速率可根据配方进行精确调控。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1781061754017-000001
    Figure REF-OBJ-1781061754017-000001
  • Figure REF-OBJ-1781061754017-000002
    Figure REF-OBJ-1781061754017-000002
  • Figure REF-OBJ-1781061754017-000003
    Figure REF-OBJ-1781061754017-000003
Patent Text Reader

Abstract

The present application belongs to the field of functional polymer materials, and particularly relates to a modified additive composition for seawater-degradable plastics, further relates to a master batch made of the same, and application of the master batch in preparing modified plastic products. The modified additive composition comprises (A) a resin matrix, (B) a non-enzymatic hydrolysis accelerator, (C) an enzymatic hydrolysis accelerator, and (D) a surface hydrolysis inhibitor. By modifying the conventional biodegradable plastics with the modified additive composition of the present application, the degradation performance of the latter in seawater environment can be improved, and the degradation time spectrum of the latter can be controlled, so that the degradation process can be started quickly after use. Since the present application provides the composition in the form of a modified additive or a master batch, the processing process and equipment of the conventional biodegradable plastics do not need to be changed, and the present application is compatible with the existing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional polymer materials, specifically relating to a modified additive composition for seawater-degradable plastics, further relating to masterbatch made therefrom, and its application in the preparation of modified plastic products. Background Technology

[0002] Marine plastic pollution has become a global environmental crisis. Conventional plastics (such as polyethylene (PE) and polypropylene (PP) have extremely high chemical inertness in their carbon-carbon backbones, resulting in natural degradation cycles in marine environments that can take hundreds of years, leading to persistent "white pollution." Against this backdrop, biodegradable plastics are considered promising alternatives, with polylactic acid (PLA) and polybutylene adipate terephthalate (PBAT) being two widely recognized examples. PLA can be decomposed into carbon dioxide and water by microorganisms under specific conditions such as composting; PBAT, as an aliphatic-aromatic copolyester, combines good mechanical properties with high biodegradability, and under suitable conditions, it can gradually break down through microbial action, exhibiting a relatively faster degradation capacity.

[0003] Biodegradation of polymer materials is a multi-stage process: (1) non-enzymatic hydrolysis: water molecules attack polymer chains, initiating initial chain breakage; (2) enzymatic hydrolysis: extracellular enzymes secreted by microorganisms further decompose the broken polymer chains into oligomers and monomers; (3) final biodegradation (mineralization): microorganisms absorb and metabolize small molecule products into carbon dioxide, water, and biomass. Therefore, the actual degradation efficiency of biodegradable materials such as PLA and PBAT is highly dependent on environmental conditions. Although they degrade well in industrial composting, their degradation performance decreases significantly in marine environments with low temperature, high salinity, and limited microbial activity. Studies show that the annual mass loss rate of these materials in seawater is usually less than 3%. This is mainly because the low temperature, neutral pH, and high salinity conditions of the ocean jointly inhibit the rate of non-enzymatic hydrolysis of the materials; at the same time, the limited microbial diversity and enzyme activity also hinder the subsequent enzymatic degradation process, resulting in near-stagnation of overall degradation. It can be seen that in real marine applications, the biodegradability of these materials is far from ideal.

[0004] On the other hand, biodegradable materials face a core contradiction in practical applications: the material must maintain sufficient mechanical properties during its service life to meet usage requirements, while simultaneously initiating rapid degradation after disposal. Existing technologies typically struggle to achieve an effective balance between processing performance, service life stability, and post-disposal degradation rate. A universally applicable and economical solution is still lacking, capable of simultaneously meeting these mutually constraining performance requirements through adjustable parameters without modifying existing production equipment. Summary of the Invention

[0005] To address the shortcomings of existing technologies, one objective of this invention is to provide a modified additive composition for seawater-degradable plastics. This modified additive composition has a time-triggered and dynamic equilibrium mechanism, aiming to achieve stable performance of plastic products during their service life and rapid, controllable, and complete degradation after being discarded into the seawater environment. This solves the core problems of existing marine degradation technologies, such as low degradation efficiency, inability to balance service life performance and degradation rate, and poor compatibility with existing processing technologies.

[0006] Specifically, the modified additive composition for seawater-degradable plastics of the present invention contains the following components in parts by weight: (A) Resin matrix: 30-85, (B) Non-enzymatic hydrolysis accelerator: 8-40, (C) Enzymatic hydrolysis accelerator: 8-40, (D) Surface hydrolysis inhibitor: 0.1-5, (E) Other functional additives: 0-10; The total amount of (B) non-enzymatic hydrolysis accelerator and (C) enzymatic hydrolysis accelerator is 10-70 parts, preferably 16-70 parts.

[0007] By modifying conventional biodegradable plastics using the modified additive composition of this invention, not only can the degradation performance of the latter in seawater environments be improved, but the degradation time spectrum can also be controlled, ensuring stability throughout the service life and enabling rapid initiation of the degradation process after use. Since this invention provides the composition in the form of modified additives (and masterbatches made therefrom), no modifications to the processing flow and equipment of conventional biodegradable plastics are required, making it perfectly compatible with existing processes.

[0008] While not wishing to be bound by any theoretical analysis, nor to be considered a limitation of the technical solution of this invention, the modified additive composition of this invention achieves the aforementioned effects. A reasonable explanation lies in the synergistic effect between the "hydrolysis promoting system" (i.e., (B) non-enzymatic hydrolysis accelerator and (C) enzymatic hydrolysis accelerator) and the "surface hydrolysis inhibitor" (i.e., (D) surface hydrolysis inhibitor), namely, dynamic antagonism and temporal synergistic effect, thus constructing an intelligent degradation system of "internal acceleration and surface slow release". During the service life of the material, the system maintains stable performance through the surface hydrophobic layer. After the service life ends, the surface inhibitor layer fails due to physical wear or environmental aging, and the highly dispersed accelerator system inside is activated, thereby initiating a rapid and thorough degradation process.

[0009] In a preferred embodiment, the modified additive composition for seawater-degradable plastics of the present invention contains, by weight, the following components: (A) Resin matrix: 40-75, (B) Non-enzymatic hydrolysis accelerator: 10-30, (C) Enzymatic hydrolysis accelerator: 10-30, (D) Surface hydrolysis inhibitor: 0.3-2, (E) Other functional additives: 0-10; The total amount of (B) non-enzymatic hydrolysis accelerator and (C) enzymatic hydrolysis accelerator is 20-60 parts.

[0010] In the modified additive composition of the present invention, the (A) resin matrix is ​​not particularly limited, and can be any biodegradable polymer material disclosed in the prior art, such as polylactic acid (PLA), polybutylene terephthalate (PBAT), polybutylene succinate (PBS), polybutylene succinate-lactic acid copolyester (PBSL), polybutylene succinate-glycolic acid copolyester (PBSG), polybutylene terephthalate-succinate (PBST), polyhydroxyalkanoate (PHA), polycaprolactone (PCL), etc. Specifically, the (A) resin matrix can be one of the above-mentioned biodegradable polymer materials, or a combination of two or more. In the present invention, the core function of the (A) resin matrix is ​​to provide a highly efficient dispersion substrate for (B) non-enzymatic hydrolysis accelerator and (C) enzymatic hydrolysis accelerator, and to dominate the degradation process through multiple synergistic mechanisms.

[0011] Similarly, we do not wish to be bound by any theoretical analysis or to consider it a limitation of the present invention. A reasonable analysis of the mechanism of action of the resin matrix in (A) is as follows: (1) Dispersion substrate and support mechanism: (A) The resin matrix and (B) both the non-enzymatic hydrolysis accelerator and (C) the enzymatic hydrolysis accelerator have good interfacial compatibility. Resin molecules can be effectively encapsulated by hydrogen bonds and van der Waals forces. The ester bonds on its molecular chain can form dipole interactions with the surface of the accelerator, effectively isolating and preventing the accelerator from agglomerating in the hydrophobic polyester matrix, ensuring that it is uniformly dispersed in the form of primary particles. This highly dispersed state greatly increases the contact reaction area between the accelerator and water molecules, improving the reaction efficiency. The microscopic encapsulated physical environment can improve the thermal and chemical stability of inorganic and organic accelerator particles during the melting process, further supporting the long-term activity of the catalyst.

[0012] (2) Autocatalysis and microenvironment regulation mechanism: (A) The resin matrix itself can participate in and dominate the catalytic reaction. For example, the hydrolysis of ester bonds can continuously release carboxylic acids (-COOH), forming an acidic microenvironment inside the material, which automatically catalyzes the acid decomposition and breakage of the polyester backbone. This mechanism can form a synergistic or sequential reaction with the alkaline catalytic mechanism of non-enzymatic promoters: initially, alkaline powders such as Ca(OH)2 maintain rapid alkaline hydrolysis, and later, the acid generated by the degradation of the resin matrix neutralizes the alkaline environment and continues to catalyze, thereby achieving seamless connection of degradation motive force and maintaining a high reaction rate.

[0013] (3) Degradation controllability design mechanism: By optimizing the composition and structure of materials, precise control of the degradation rate can be achieved. Under this mechanism, (A) the selection of the resin matrix, (B) the ratio of non-enzymatic hydrolysis accelerators, (C) the ratio of enzymatic hydrolysis accelerators, the type of polymer, and its chemical properties can all be adjusted. These adjustments help to achieve dynamic release of the accelerator in the matrix, ensuring that its release rate matches environmental conditions (such as temperature and humidity). Gradual regulation of the material degradation rate from several weeks to several years can be achieved to meet the needs of different application scenarios, from short-term commercial packaging to medium-term agricultural mulch films and seawater-degradable plastics.

[0014] In a preferred embodiment, the resin matrix of the present invention is selected from one or more combinations of the following components: polylactic acid (PLA), polybutylene terephthalate (PBAT), polybutylene succinate (PBS), polybutylene succinate-lactic acid copolyester (PBSL), and polybutylene succinate-glycolate copolyester (PBSG). Polybutylene terephthalate (PBAT) is further preferred.

[0015] In addition to using a specific (A) resin matrix, this invention creatively combines two types of hydrolysis accelerators, (B) non-enzymatic hydrolysis accelerators and (C) enzymatic hydrolysis accelerators, to further utilize their synergistic effect and better take advantage of the characteristics of the seawater environment to achieve precise control of the degradation rate. The (B) non-enzymatic hydrolysis accelerator of the present invention is not particularly limited as long as it is an inorganic base or its precursor that can react with water to generate an alkaline substance or directly provide an alkaline environment. Alkaline earth metal oxides, hydroxides and their complexes can be listed. In one embodiment, the (B) non-enzymatic hydrolysis accelerator of the present invention is selected from one or more of the following components: calcium oxide (CaO), calcium hydroxide (Ca(OH)2), magnesium oxide (MgO), and magnesium hydroxide (Mg(OH)2). Using inorganic powder as the (B) non-enzymatic hydrolysis accelerator to regulate the hydrolysis reaction kinetics has become an effective technical path to improve the efficiency of seawater degradation. Similarly, it is not desired to be subject to any constraints. Reasonable mechanism analysis includes: (1) thermal effect mechanism, such as calcium oxide (CaO) reacting with water to undergo a violent exothermic reaction, generating Ca(OH)2 and releasing a large amount of heat energy, causing the local temperature of the material to rise instantaneously and accelerating the ester bond breaking; (2) alkaline catalytic mechanism, such as Ca(OH)2 releasing OH after hydrolysis. - Ions, increase local pH, catalyze the hydrolysis of polyester ester bonds through nucleophilic attack, and neutralize the carboxylic acid released, avoiding the inhibition of microbial activity by acidic environment, while maintaining alkaline catalytic conditions; (3) Adjustable design, including particle size control, generally speaking (B) the average particle size (D50) of non-enzymatic hydrolysis accelerator should be less than 50 μm, preferably not more than 25 μm, and even more preferably not more than 10 μm; In a preferred embodiment, CaO particles with an average particle size not more than 25 μm are used so that they can be uniformly dispersed and avoid agglomeration, thereby obtaining a larger specific surface area, greatly improving the hydrolysis promotion efficiency and the control effect of the composite system.

[0016] In addition to the non-enzymatic hydrolysis accelerator (B), this invention further incorporates an enzymatic hydrolysis accelerator (C). The specific type of this accelerator is not limited, as long as it can be preferentially utilized by marine microorganisms to support their growth and degradation of plastics. Examples include natural organic polymers or their derivatives. In one embodiment, the enzymatic hydrolysis accelerator (C) of this invention is selected from one or more combinations of the following components: alginate oligosaccharides, rhamnolipids, poly-γ-glutamic acid, trehalose, β-cyclodextrin, sodium alginate, starch, cellulose, lignin, chitin, sucrose, fructose, and whey protein powder. Preferably, alginate oligosaccharides, rhamnolipids, poly-γ-glutamic acid, trehalose, β-cyclodextrin, and sodium alginate are used. The use of the enzymatic hydrolysis accelerator (C) can construct a channel for efficient reaction between enzyme molecules and polymeric substrates, significantly accelerating the biodegradation process. Similarly, we do not want to be subject to any constraints. Reasonable mechanism analysis includes: (1) "Primer effect" and active induction of biofilm. Unlike the passive supply of conventional nutrients, the specific components selected in this invention (such as alginate oligosaccharides and rhamnolipids) act as signal molecules for microbial quorum sensing. They can specifically recruit marine dominant degrading bacteria (such as Vibrio and Pseudomonas) through chemotaxis and induce them to secrete extracellular polymers (EPS), thereby rapidly constructing a highly active biofilm on the hydrophobic polyester surface. Through the cometolytic mechanism, the concentration of non-specific esterases and depolymerases enriched in the biofilm is significantly increased, thereby launching a high-intensity enzymatic attack on the polymer matrix. (2) Osmotic pressure cracking and interfacial wetting (physicochemical mechanism): not limited to the isolated solubility defect effect of conventional fillers such as starch and sucrose. Some specific components (such as poly-γ-glutamic acid, rhamnolipids, and β-cyclodextrin) have unique amphiphilic or superabsorbent properties. In the seawater environment, the migration of amphiphilic molecules to the interface significantly reduces the surface energy of the material, allowing seawater to quickly wet the material surface; at the same time, highly absorbent components such as poly-γ-glutamic acid absorb water and swell inside the matrix, forming a high osmotic pressure "micro-water sac", and the resulting expansion stress physically breaks the polymer matrix; the "externally hydrophilic and internally hydrophobic" ring cavity structure of β-cyclodextrin constructs a "molecular tunnel" for water molecules to migrate into the hydrophobic polyester matrix, generating a large number of cracks at the microscale, which greatly increases the contact area between the enzyme and the polymer chain. (3) Microenvironment regulation and stress protection (environmental adaptation mechanism): In response to the characteristics of high salinity and low nutrient content (high carbon / nitrogen ratio) in the marine environment, specific factors in the components (such as trehalose and nitrogen-containing polymers) play a key regulatory role. Trehalose, as a stress protection factor, assists attached microorganisms in resisting the high osmotic pressure stress of seawater; while the degradation of nitrogen-containing components balances the carbon / nitrogen ratio of the microenvironment in situ, eliminates the limiting factors for microbial growth, and ensures a continuous positive feedback loop of biodegradation.

[0017] To further improve the degradation time of the modified additive composition of the present invention, in addition to adding (B) a non-enzymatic hydrolysis accelerator and (C) an enzymatic hydrolysis accelerator to (A) the resin matrix, it is also necessary to add (D) a surface hydrolysis inhibitor. Its functions include: (1) acting as a lubricant to reduce melt viscosity, reduce frictional heat during processing, and avoid thermal degradation; (2) simultaneously forming a hydrophobic film on the material surface through a co-extrusion process (interface effect, rheological properties, etc.), delaying initial water penetration. The surface hydrolysis inhibitor can effectively increase the mechanical functional cycle of the material through negative feedback. In a preferred embodiment, the (D) surface hydrolysis inhibitor of the present invention is polyethylene wax (PELD wax, PE wax).

[0018] In addition to the aforementioned components (A)-(D), the modified additive composition of the present invention may, if necessary, further add (E) other functional additives according to the application requirements, such as: processing functional additives, such as plasticizers, compatibilizers, heat stabilizers, etc.; and application functional additives, such as flame retardants, antistatic agents, conductive agents, rodent repellents, etc.

[0019] The modified additive composition of the present invention is preferably provided in the form of a "masterbatch". Therefore, another object of the present invention is to provide a method for preparing the masterbatch of the modified additive composition, comprising the following steps: S01. Pretreatment: Dry the components of the modified additive composition for later use, and / or prepare the dried materials for later use; S02, Premixing: The components pretreated in step S01 are added to the mixer according to the dosage ratio to make them macroscopically uniform, thus obtaining a premixed material; S03, Melt Blending Extrusion: The premixed material from step S02 is fed into an extruder and extruded to obtain a melt strip; S04, Cooling and Granulation: After cooling the melt strip from step S03, it is granulated to obtain masterbatch.

[0020] In a preferred embodiment, in step S01, each component is vacuum dried at 60-80°C until the moisture content is below 300 ppm.

[0021] In a preferred embodiment, in step S02, each component is dry-mixed in a high-speed mixer at a speed of 300-800 rpm for 5-10 minutes.

[0022] In a preferred embodiment, in step S03, a co-rotating twin-screw extruder is used, with a screw speed of 150-300 rpm within a temperature range of 110-150°C. During this process, the melt temperature of the material is maintained at 140-160°C, achieving efficient dispersion at the microscale.

[0023] Another object of the present invention is to provide an application of the aforementioned modified additive composition and / or its masterbatch for the modification of biodegradable materials. In one embodiment, the aforementioned modified additive composition and / or its masterbatch is melt-blended with a target matrix resin at a mass ratio of 1:9 to 1:1; preferably, at a mass ratio of 2:9 to 1:1. The target matrix resin of the present invention is not particularly limited and may be the same as or different from the resin matrix (A) in the modified additive composition, and will not be described further. In a further embodiment, the aforementioned modified additive composition and / or its masterbatch is melt-blended with a target matrix resin using standard plastic processing equipment (such as an extruder, injection molding machine, blown film machine) to prepare a final product, such as a film, sheet, fiber, injection molded part, etc., in a one-step process. The processing temperature is set according to the characteristics of the matrix resin; for example, for PBS substrates, it may be in the range of 140-170°C.

[0024] The beneficial effects of this invention are as follows: Highly efficient and time-controllable degradation: The unique "internal acceleration, surface slow release" mechanism achieves an intelligent response of "stable service first, then rapid degradation." Through triple synergy, the degradation cycle of materials in seawater can be shortened from several years to several weeks, and the rate can be precisely controlled according to the formulation.

[0025] A perfect balance between performance and degradation: The innovative introduction of surface hydrolysis inhibitors ensures that the material maintains excellent mechanical properties within its set service life, solving the pain point of traditional degradable materials that are either "not degradable or not durable".

[0026] Strong environmental adaptability: The unique non-enzymatic / enzymatic composite acceleration pathway effectively overcomes the limitations of low temperature, high salinity and low microbial activity in the seawater environment, providing a stable and reliable degradation driving force.

[0027] With broad application prospects: It is provided in ready-to-use masterbatch form, is fully compatible with existing plastic processing technologies, and requires no equipment modification. This method is applicable to a variety of mainstream resins such as PLA, PBAT, PBS, and PBSL, and its application range is extremely wide. Detailed Implementation

[0028] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0029] Preparation Example 1: Masterbatch of Modified Auxiliary Composition (A) resin matrix, (B) non-enzymatic hydrolysis accelerator, (C) enzymatic hydrolysis accelerator, (D) surface hydrolysis inhibitor, and necessary (E) other functional additives were placed in an environment of (60±2)℃ and a vacuum degree not exceeding -0.095 MPa for vacuum drying for 6 hours, controlling the material moisture content to be below 300 ppm. The raw materials of each component were weighed according to the material dosage ratio of each embodiment and added to a high-speed mixer. The mixture was stirred at 500 rpm for 8 minutes to ensure thorough and uniform dispersion of each component, resulting in a premixed material.

[0030] The premixed materials are fed into a co-rotating twin-screw extruder for melt blending. The temperatures from zone one to the die head are set sequentially to 110-130℃, 130-135℃, and 135-145℃, and the melt temperature is maintained at (145±5)℃. Extrusion is carried out at a main extruder speed of 200 rpm. The melt-extruded strands are immediately cooled by a circulating water bath at (10±2)℃, and finally cut by a pelletizer to obtain uniform cylindrical masterbatches with a diameter of about 2-3 mm.

[0031] Preparation Example 2: Biodegradable Materials Modified with Modified Auxiliary Composition Masterbatch The modified additive composition masterbatch obtained in Preparation Example 1 and the target matrix resin were fed into a high-speed mixer according to the material dosage ratio of each example. After being mixed evenly, the mixture was fed into a twin-screw extruder for modified melt blending. The temperature of each temperature zone was set at 130-160°C and the screw speed was controlled at 80 rpm. Subsequently, it was injection molded into a standard test specimen.

[0032] Performance testing Initial properties: tensile strength, modulus of elasticity, elongation at break (ASTM D638); Marine environmental performance simulation: conducted in artificial seawater at 25±2℃.

[0033] Mechanical strength retention rate: Tensile strength was tested after 6 months and the retention rate was calculated.

[0034] Degradation weight loss rate: The weight loss rate was tested at 6 months and 12 months, respectively.

[0035] Series 1: Modified PBAT (Polybutylene adipate / Terephthalate) Example E1-1 The modified additive composition uses the following raw materials and the amounts shown in Table 1: (A) Resin matrix: PBAT 50g, (B) Non-enzymatic hydrolysis accelerator: Calcium hydroxide (10μm) 25g, (C) Enzymatic hydrolysis accelerator: β-cyclodextrin 25g, (D) Surface hydrolysis inhibitor: polyethylene wax, 1g.

[0036] Following the steps of Preparation Example 1, a modified additive composition was first prepared to obtain 101g of masterbatch. Subsequently, according to the amounts shown in Table 1-1, 40g of masterbatch and 60g of target matrix resin PBAT were weighed, and according to the steps of Preparation Example 2, a standard test strip of the modified biodegradable material was obtained. The ratio of each component, i.e., all matrix resin: non-enzymatic hydrolysis accelerator: enzymatic hydrolysis accelerator: surface hydrolysis inhibitor, was 80:10:10:0.4, wherein all matrix resin includes (A) resin matrix and target matrix resin contained in the masterbatch.

[0037] Examples E1-2 to E1-5 Based on E1-1, the dosage of relevant components in the modified additive composition is changed, as shown in Table 1-1, while the rest is the same as E1-1.

[0038] Examples E1-6 Based on E1-1, replace calcium hydroxide in component B with calcium oxide, and the rest is the same as E1-1.

[0039] Examples E1-7 Based on E1-1, the β-cyclodextrin in component C is replaced with sodium alginate, and the rest is the same as E1-1.

[0040] Examples E1-8 Based on Example E1-1, instead of preparing a modified additive composition (masterbatch) (but retaining pretreatment such as material drying), the raw materials of the masterbatch are fed together with the target matrix resin, and standard test strips are obtained according to the steps of Preparation Example 2.

[0041] Comparative Example CE1-1 As a blank control, without adding the modified additive composition (masterbatch) (but retaining the pretreatment such as material drying), 100g of the target matrix resin (i.e. PBAT) was used to obtain standard test strips according to the steps of Preparation Example 2.

[0042] Comparative Examples CE1-2~CE1-3 According to the material dosage ratio shown in Table 1-1, that is, in the modified additive composition formulation, component B or C is removed and replaced with an equal amount of component C or B to make up the total amount of raw materials of the modified additive composition so that the total remains unchanged. Otherwise, it is the same as in Example E1-1, and standard test strips are prepared.

[0043] Comparative Example CE1-4 Based on Example E1-1, component D was removed, and otherwise the preparation was the same as in Example E1-1 to obtain the standard test strip.

[0044] Comparative Examples CE1-5~CE1-6 According to the material dosage ratio shown in Table 1-1, that is, high-concentration concentrated masterbatch (CE1-5) and masterbatch with insufficient content of components B and C (CE1-6) are used respectively. By adjusting the dosage ratio of masterbatch to target matrix resin, the content ratio of each material in the standard test strip is the same as that in Example E1-1.

[0045] Comparative Example CE1-7 Based on Example E1-1, the amount of (D) surface hydrolysis inhibitor (i.e., polyethylene wax) was increased from 1g to 5g, otherwise it was the same as Example E1-1, and a standard test strip was prepared.

[0046] Comparative Example CE1-8 Based on E1-1, the particle size of calcium hydroxide in component B is replaced from 10 μm to 50 μm, and the rest is the same as E1-1.

[0047] The performance of the modified biodegradable materials in the above embodiments and comparative examples is shown in Tables 1-2.

[0048] Table 1-1 Series 1 Material Proportions Table 1-2 Performance of Series I Modified Biodegradable Materials Examples E1-1 to E1-8 demonstrate that, within the scope of patent protection of this invention, modified materials with mechanical properties similar to or improved upon the control group CE1-1 were successfully obtained, while significantly improving seawater degradability. In a 3-month seawater immersion experiment, the degradation weight loss rate exceeded 70%.

[0049] Examples E1-2 and E1-3 demonstrate the effectiveness of controlling the degradation rate by adjusting the ratio of B+C in the masterbatch; while E1-4 and E1-5 show the effects of B and C on degradation rate and mechanical properties under different individual component ratios. The results show that inorganic powders provide more significant support for tensile strength, while component C generally performs better in maintaining the elongation at break of PBAT.

[0050] Comparative results of Examples E1-1 and E1-8 show that the modification target can be successfully achieved with and without the combination of additives of the present invention, but the effect is more significant when using pre-dispersed masterbatch.

[0051] Examples CE1-5 and CE1-6 demonstrate that when the content of components B and C in the masterbatch does not meet the requirements, secondary optimization can be performed by adjusting the mixing ratio to achieve the expected performance.

[0052] Examples CE1-7 demonstrate the effect of excess component D on the degradation rate.

[0053] Examples CE1-8 demonstrate the impact of excessively large particle size of component B powder on dispersibility, mechanical properties, and final degradation rate, indicating that particle size control is crucial to the performance of modified materials.

[0054] Examples E1-1 and CE1-2 demonstrate the necessity of component B, E1-1 and CE1-3 demonstrate the necessity of component C, and E1-1 and CE1-4 discuss the necessity of component D, all of which further support the key role of each component in the modified material.

[0055] Series 2: Modified PBS (Polybutylene Succinate) Except for: ① replacing sodium alginate in Example E1-7 with an equal amount of poly-γ-glutamic acid in component C of Example E2-7, and ② replacing PBAT in the modified biodegradable material formulation with PBS, the rest are the same as E1-1~E1-8 and Comparative Examples CE1-1~CE1-8, resulting in new Examples E2-1~E2-8 and Comparative Examples CE2-1~CE2-8, the properties of the modified biodegradable materials are shown in Table 2.

[0056] Table 2 Performance of a series of modified biodegradable materials Series 3: Modified PLA (Polylactic Acid) Except for: ① replacing sodium alginate in Example E1-7 with an equal amount of lignin in component C of Example E3-7, and ② replacing PBAT with PLA in the modified biodegradable material formulation, the rest are the same as E1-1~E1-8 and Comparative Examples CE1-1~CE1-8, resulting in new Examples E3-1~E3-8 and Comparative Examples CE3-1~CE3-8, the properties of the modified biodegradable materials are shown in Table 3.

[0057] Table 3 Performance of a series of modified biodegradable materials Series 4: Modified PBSL (Polybutylene succinate-lactic acid copolymer) Except for: ① replacing sodium alginate in Example E1-7 with an equal amount of trehalose in Component C of Example E4-7, and ② replacing PBAT in the modified biodegradable material formulation with PBSL30 (i.e., lactic acid accounts for 30% of the total molar mass of the copolymer), the rest are the same as E1-1 to E1-8 and Comparative Examples CE1-1 to CE1-8, resulting in new Examples E4-1 to E4-8 and Comparative Examples CE4-1 to CE4-8, the properties of the modified biodegradable materials are shown in Table 4.

[0058] Table 4 Performance of Series Four Modified Biodegradable Materials Series 5: Modified PCL (Polycaprolactone) Except for: ① replacing sodium alginate in Example E1-7 with an equal amount of alginate oligosaccharide in component C of Example E5-7; ② replacing calcium hydroxide in Example E1-7 with an equal amount of calcium carbonate of the same particle size in component B of Example E5-8; and ③ replacing PBAT with PCL in the modified biodegradable material formulation, the rest are the same as E1-1 to E1-8 and Comparative Examples CE1-1 to CE1-8, resulting in new Examples E5-1 to E5-8 and Comparative Examples CE5-1 to CE5-8, the properties of the modified biodegradable materials are shown in Table 5.

[0059] Table 5 shows the performance of four series of modified biodegradable materials. As shown in Tables 2 to 5, the modified additive composition and modification method provided by this invention are applicable to a variety of biodegradable resins. By adjusting the type and proportion of additives, precise control over the mechanical properties and degradation rate of the material can be achieved, thereby meeting the needs of different application scenarios. This invention has significant technical advantages and broad application prospects.

[0060] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A modified additive composition for seawater-degradable plastics, characterized in that, The composition contains the following components in parts by weight: (A) Resin matrix: 30-85, (B) Non-enzymatic hydrolysis accelerator: 8-40, (C) Enzymatic hydrolysis accelerator: 8-40, (D) Surface hydrolysis inhibitor: 0.3-2, (E) Other functional additives: 0-10; The total amount of (B) non-enzymatic hydrolysis accelerator and (C) enzymatic hydrolysis accelerator is 10-70 parts. The (B) non-enzymatic hydrolysis accelerator is selected from one or a combination of two of calcium oxide (CaO) and calcium hydroxide (Ca(OH)2). The (C) enzymatic hydrolysis accelerator is selected from one or more of the following components: poly-γ-glutamic acid, alginate oligosaccharides, rhamnolipids, trehalose, β-cyclodextrin, and sodium alginate. The surface hydrolysis inhibitor (D) is polyethylene wax. The average particle size of the (B) non-enzymatic hydrolysis accelerator is ≤25μm.

2. The modified additive composition for seawater-degradable plastics according to claim 1, characterized in that, The composition contains the following components in parts by weight: (A) Resin matrix: 40-75, (B) Non-enzymatic hydrolysis accelerator: 10-30, (C) Enzymatic hydrolysis accelerator: 10-30, (D) Surface hydrolysis inhibitor: 0.3-2, (E) Other functional additives: 0-10; The total amount of (B) non-enzymatic hydrolysis accelerator and (C) enzymatic hydrolysis accelerator is 20-60 parts.

3. The modified additive composition for seawater-degradable plastics according to claim 1 or 2, characterized in that, The resin matrix (A) is selected from one or more of the following components: polylactic acid (PLA), polybutylene terephthalate (PBAT), polybutylene succinate (PBS), polybutylene succinate-lactic acid copolyester (PBSL), and polybutylene succinate-glycolate copolyester (PBSG).

4. A modified masterbatch for seawater-degradable plastics, characterized in that, The masterbatch is prepared from the modified additive composition for seawater-degradable plastics as described in any one of claims 1 to 3.

5. The method for preparing modified masterbatch for seawater-degradable plastics as described in claim 4, characterized in that, The method includes the following steps: S01. Pretreatment: Dry the components of the modified additive composition for later use, and / or prepare the dried materials for later use; S02, Premixing: The components pretreated in step S01 are added to the mixer according to the dosage ratio to make them macroscopically uniform, thus obtaining a premixed material; S03, Melt Blending Extrusion: The premixed material from step S02 is fed into an extruder and extruded to obtain a melt strip; S04. Cooling and granulation: The melt strip from step S03 is cooled and then granulated to obtain the masterbatch.

6. A modified biodegradable material, characterized in that, The modified biodegradable material is a melt blend of the modified additive composition for seawater-degradable plastics according to any one of claims 1 to 3 and / or the modified masterbatch for seawater-degradable plastics according to claim 4 with a target matrix resin at a mass ratio of 1:9 to 1:

1. The target matrix resin is selected from one or more of the following components: polylactic acid (PLA), polybutylene terephthalate (PBAT), polybutylene succinate (PBS), polybutylene succinate-lactic acid copolyester (PBSL), and polybutylene succinate-glycolate copolyester (PBSG).

Citation Information

Patent Citations

  • Biodegradable nanometer filling function master batch and preparation method and application thereof

    CN105802168A

  • Physical modified starch suitable for tray, full-degradable composite material and preparation method of composite material

    CN112961408A

  • Recycled biodegradable plastic additive, biodegradable recycled fibers and method of making same

    US20230081428A1